2021
DOI: 10.1101/2021.07.14.452205
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

R-loop-induced p21 expression following CDC73, CTR9, and PAF1 loss protects cancer cells against replicative catastrophe following WEE1 inhibition

Abstract: WEE1 inhibitors have now advanced into clinical studies as monotherapy or in combination with chemoradiotherapy in TP53, RAS, BRAF, and SETD2 mutation carriers across several tumour types, yet mechanisms of resistance are still poorly understood. Here, we further elucidate the mechanisms by which AZD1775, the most potent WEE1 inhibitor, kills cells and reveal additional genetic interactions that can result in resistance, but could be used to optimise its clinical utility. We identified RNA Polymerase II-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In line, recruitment of PAF1c to MYC was recently shown to be dependent on the Huwe1 ubiquitin ligase and suggested to mediate DNA repair at transcription start sites ( 26 ). However, other studies found that PAF1c can lead to the accumulation of R-loops and promote genomic instability under replicative stress ( 30 , 31 ). We show that ectopic stabilization of MYC by monomeric USP28 stimulates recruitment of PAF1c and resolution of TRCs to drive ectopic DNA synthesis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In line, recruitment of PAF1c to MYC was recently shown to be dependent on the Huwe1 ubiquitin ligase and suggested to mediate DNA repair at transcription start sites ( 26 ). However, other studies found that PAF1c can lead to the accumulation of R-loops and promote genomic instability under replicative stress ( 30 , 31 ). We show that ectopic stabilization of MYC by monomeric USP28 stimulates recruitment of PAF1c and resolution of TRCs to drive ectopic DNA synthesis.…”
Section: Discussionmentioning
confidence: 95%
“…Mechanistically, PAF1c stimulates ubiquitination of histone H2B ( 29 ), which in turn stabilizes replication forks and promotes homologous recombination. However, PAF1c can also lead to accumulation of R-loops and stimulate ATR signaling exacerbating replicative stress ( 30 , 31 ), indicating that the function of PAF1c in genome stability depends on genetic or signaling context.…”
Section: Introductionmentioning
confidence: 99%